Unitarity of the SoV Transform for $SL(2,\mathbb C)$ Spin Chains - Manashov, Alexander N. (Symmetry, integrability and geometry, methods and applications, 2023)
We prove the unitarity of the separation of variables transform for $SL(2,\mathbb C)$ spin chains by a method based on the use of Gustafson integrals.